Specific absorption rate reduction using nonlinear gradient fields. Issue 2 (17th September 2012) - Kopanoglu, Emre; Yilmaz, Ugur; Gokhalk, Yildiray; Atalar, Ergin
<x xml:space="preserve">Abstract</x> The specific absorption rate is used as one of the main safety parameters in magnetic resonance imaging. The performance of imaging sequences is frequently hampered by the limitations imposed on the specific absorption rate that increase in severity at higher field strengths. The most well‐known approach to reducing the specific absorption rate is presumably the variable rate selective excitation technique, which modifies the gradient waveforms in time. In this article, an alternative approach is introduced that uses gradient fields with nonlinear variations in space to reduce the specific absorption rate. The effect of such gradient fields on the relationship between the desired excitation profile and the corresponding radiofrequency pulse is shown. The feasibility of the method is demonstrated using three examples of radiofrequency pulse design. Finally, the proposed method is compared with and combined with the variable rate selective excitation technique. Magn Reson Med 70:537–546, 2013. © 2012 Wiley Periodicals, Inc.